Patterns of Business Creation, Survival and Growth : Evidence from Africa - Klapper, Leora; Richmond, Christine (2012)
The authors study firm dynamics using a novel database of all formally registered firms in Cote d'Ivoire from 1977 to 1997, which account for about 60 percent of gross domestic product. First, they examine entry and exit patterns and the role of new and exiting firms versus incumbents in job creation and destruction. They find that while the rate of job creation at new firms is quiet high -- at 8 percent on average -- the number of jobs added by new firms is small in absolute terms. Next, they examine survival rates and find that the probability of survival increases monotonically with firm size, but manufacturing and foreign-owned firms face higher likelihoods of exit compared with service oriented and domestically owned firms. They find that higher growth of gross domestic product increases the probability of firm survival, but this is a broad impact with no firm size disproportionately affected. In robustness checks, they find that after 1987 size is no longer a significant determinant of firm survival for new entrants, suggesting that the operating environment for firms changed. Finally, they find that trade and fiscal reform episodes raised the probability of firm exit and attenuated the survival disadvantages faced by smaller firms, but exchange rate revaluation and pro-private sector reforms did not significantly lower the likelihood of exit.